Memperkuat Kinerja Keuangan UMKM: Explorasi Peran Kepemimpinan Transformasional Digital dan Ketangkasan Organisasi - Putri, Hidayatna; Siagian, Hendra Sakti Putra; Octoyuda, Edgar; Chairia; Sari, Ria Nelly (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Leadership engagement and organisational agility are crucial for organisations in enhancing their performance, particularly in terms of financial performance. This study investigates how digital transformational leadership contributes to enhancing the financial performance of micro, small, and medium enterprises (MSMEs) by fostering organisational agility. Nevertheless, there is a lack of extensive research on the significance of digital transformational leadership, particularly within the context of MSMEs. This study specifically examines MSMEs located in North Sumatra. The sample size for this study consists of 138 employees from various organisation. The chosen analytical approach is Structural Equation Modelling (SEM), which is employed to examine the relationship between the variables under investigation. The research findings indicate that both digital transformational leadership and organisational agility have a substantial and beneficial influence on financial performance. Furthermore, it is observed that digital transformational leadership has a good impact on organisational agility. Organisational agility serves as a powerful intermediary in the connection between digital transformative leadership and enhanced financial performance of MSMEs. This study offers theoretical and practical advice for researchers and managers who are interested in devising methods to enhance financial performance in the MSME sector by implementing digital transformational leadership and fostering organisational agility. This study also examines other theoretical and practical contributions, and future research objectives. Keywords: Digital Transformastional Leadership; Organizational Agility; Financial Performance; MSME.